2019
DOI: 10.31958/js.v10i1.1216
|View full text |Cite
|
Sign up to set email alerts
|

JENIS-JENIS BELALANG ( Orthoptera: Ensifera ) PADA KAWASAN OBJEK WISATA AIR PANAS SAUMAN DESA RAMBAH TENGAH HULU KAB.ROKAN HULU

Abstract: This research aims to determine the species of grasshoppers (Orthoptera: Ensifera) located in Sauman hotsprings tourism object in the village of Rambah Tengah Hulu sub district of Rambah Rokan Hulu district. This study was conducted from December 2017 to March 2018 by survey method. Grasshopper obtained was then identified by describing the species based reference source. Result soft hestudy founda Grasshopper derived from 3 families, 7 subfamily, 8 genera and 10 species. As for the species of grasshoppers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Rentz stated that the number of grasshoppers (Orthoptera) species identified more than 2,000 species [3]. However, the research results show that the existence of species found is very small, usually only numbering dozens.…”
Section: Introductionmentioning
confidence: 98%
“…Rentz stated that the number of grasshoppers (Orthoptera) species identified more than 2,000 species [3]. However, the research results show that the existence of species found is very small, usually only numbering dozens.…”
Section: Introductionmentioning
confidence: 98%